1997
DOI: 10.1089/gte.1997.1.165
|View full text |Cite
|
Sign up to set email alerts
|

An Allelic Variant at theATMLocus Is Implicated in Breast Cancer Susceptibility

Abstract: We have tested a simple procedure, disease association by locus stratification, for identifying breast cancer patients with pathogenetic allelic variants at several candidate loci. The strategy was based on the assumption of epistatic interactions of the candidates. We analyzed 66 independent cases from sib pairs affected with breast cancer that had previously been collected during an investigation of pathogenetic-allele-sharing at the HRAS1 mini-satellite locus. An exon 24 polymorphism of ATM, substituting ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…There may be additional, yet undetermined, factors that influence the contralateral breast cancer risk. Some of the known putative genetic modifiers include ATM mutations, rare H-ras alleles or androgen receptor gene variations (Phelan et al, 1996;Larson et al, 1998;Rebbeck et al, 1999;Broeks et al, 2000). We have presently no evidence that bilaterality of breast cancer alone were a strong indicator of BRCA1 and BRCA2 mutations if adjusted for age and family history.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…There may be additional, yet undetermined, factors that influence the contralateral breast cancer risk. Some of the known putative genetic modifiers include ATM mutations, rare H-ras alleles or androgen receptor gene variations (Phelan et al, 1996;Larson et al, 1998;Rebbeck et al, 1999;Broeks et al, 2000). We have presently no evidence that bilaterality of breast cancer alone were a strong indicator of BRCA1 and BRCA2 mutations if adjusted for age and family history.…”
Section: Discussionmentioning
confidence: 73%
“…We thus investigated whether more common missense substitutions of BRCA1 or BRCA2 might play a role as predisposing factors towards contralateral cancer. Missense substitutions in other tumour suppressor genes have been described as lowpenetrance mutations that may predispose to certain malignancies or modify disease progression (Larson et al, 1998;Otterson et al, 1999;Varley et al, 1999; Lumin et al, 2000;Rebbeck et al, 2000), and a few missense variants of the BRCA1 and BRCA2 proteins, including the Gln356Arg, Arg841Trp and Leu871Pro substitutions of BRCA1 and the Asn372His substitution of BRCA2, have previously been implicated in the susceptibility to breast or ovarian cancer (Barker et al, 1996;Durocher et al, 1996;Dunning et al, 1996;Healey et al, 2000). However, none of the common BRCA1 and BRCA2 variants occurred at a significantly increased prevalence in our patients with bilateral cancer, nor did we find a deviation of the genotype distributions from Hardy-Weinberg equilibrium.…”
mentioning
confidence: 99%
“…This raises the possibility that, like mutations in BRCA1 itself, changes in Chk2, ATR, or ATM activity may promote genetic instability and increase susceptibility to the development of breast cancer and other tumors. A growing body of evidence has suggested that ATM mutations confer increased susceptibility to breast cancer (91)(92)(93)(94)(95). Epidemiologic studies have put the Chk2 and BRCA1 in the same breast cancer development pathway (96,97).…”
Section: Post-transcriptional Regulation Of Brca1 By Phosphorylationmentioning
confidence: 99%
“…Significant evidence exists that heterozygous ATM carriers have an elevated lifetime risk of developing breast cancer (Swift et al 1987;Athma et al 1996;Larson et al 1998); however, there is disagreement about the magnitude of this effect (Easton 1994;Bishop and Hopper 1997;Fitzgerald et al 1997). This debate is especially relevant owing to the large frequency of ATM mutation carriers, estimated to comprise ∼1.4% of the general population, who could account for up to 6.5% of all breast cancer cases (Athma et al 1996).…”
mentioning
confidence: 99%